Karakteristik Pati Sagu (Metroxylon sp.) Hasil Modifikasi Ikat Silang - Dwi Karmila Syafriyanti; Nuri Andarwulan; Purwiyatno Hariyadi; Andri J. Laksana (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
The utilization of sago starch is very low in Indonesia while sago is the starch producing plant which grows abundantly in Indonesia. In order to increase sago starch applications, such modification is needed. This research was aimed to conduct cross-linked modification upon the sago starch, thus evaluate its physicochemical characteristics. Cross-linked modifications included by varying phosphoryl chloride (POCl3) concentrations (i.e., 0–0.050%) and the reacting times (i.e, 0–60 minutes). Cross-linked modifi-cation yielded in a lower paste clarity, solubility, and swelling power and could increase peak viscosity, holding viscosity, final viscosity, setback, breakdown, gelatinization temperature, gel strength, amylose content, and gelatinization enthalpy. It is found that some granules of cross-linked starch lost its maltose cross property. Concentration of POCl3 was very influential to the change of modified starch characteristics, and the highest level of modification was achieved by 0.050% POCl3.